Interrupted Aortic Arch Complicated with Type A Aortic Dissection in a Young Adult - Ashish Dua; Arun Sharma; Rupesh Kumar; Manphool Singhal (Heart Views)
Interrupted aortic arch (IAA) is a congenital anomaly characterized by a discontinuity between the ascending and descending aorta. We present a 27-year-old male patient who had presented with Stanford Type A aortic dissection and was subsequently found to have IAA on computed tomography aortogram. The patient subsequently underwent emergency surgery for the repair of aortic dissection. Although few studies with IAA and coexistent Stanford type-B aortic dissection have been described, there is no reported case in literature on IAA with Stanford Type A aortic dissection.